2020 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2020
DOI: 10.1109/iros45743.2020.9341388
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven Characterization of Human Interaction for Model-based Control of Powered Prostheses

Abstract: This paper proposes a data-driven method for powered prosthesis control that achieves stable walking without the need for additional sensors on the human. The key idea is to extract the nominal gait and the human interaction information from motion capture data, and reconstruct the walking behavior with a dynamic model of the human-prosthesis system. The walking behavior of a human wearing a powered prosthesis is obtained through motion capture, which yields the limb and joint trajectories. Then a nominal traj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Previous studies with a similar aim of utilizing sEMG in predicting joint kinematics and kinetics conducted either a feature (e.g., Phinyomark et al, 2011) or a muscle combination selection (e.g., Wang et al, 2021), or report only the utilized feature per muscle (Phinyomark et al, 2011;Li et al, 2021). Note that, taking into account the challenging nature of determining which specific parameter or combination of parameters is responsible for an improved neural network output (Goodfellow et al, 2016), a separate evaluation of the effects of multiple parameters has been suggested (Molnar, 2020). The complexity of the neural networks can consequently be reduced for an efficient training (Kendall et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies with a similar aim of utilizing sEMG in predicting joint kinematics and kinetics conducted either a feature (e.g., Phinyomark et al, 2011) or a muscle combination selection (e.g., Wang et al, 2021), or report only the utilized feature per muscle (Phinyomark et al, 2011;Li et al, 2021). Note that, taking into account the challenging nature of determining which specific parameter or combination of parameters is responsible for an improved neural network output (Goodfellow et al, 2016), a separate evaluation of the effects of multiple parameters has been suggested (Molnar, 2020). The complexity of the neural networks can consequently be reduced for an efficient training (Kendall et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rates of these interventions are high, reaching, e.g., over 11,500 cases alone in the UK each year ( Isaacs-Itua and Sedki, 2018 ) and from 2003 to 2013, about half of those were transtibial amputations ( Ahmad et al, 2016 ). Ascribed to a simple, low economic cost and robust design, energy storing and returning prostheses with elastic and damping characteristics ( Brackx et al, 2013 ) dominate the commercial lower limb prostheses market ( Gehlhar et al, 2020 ). However, because of lack of mechanical power generation and autonomous adaptation they can only provide lower than normal gait speeds with high metabolic energy costs that leads to early fatigue ( Vucina et al, 2005 ; Brackx et al, 2013 ; Xu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The optimization yields parameters for each domain α v that define Bézier polynomials for the desired trajectories y d s,v (τ (x s ), α v ) parameterized by the state-based phase variable τ (x s ), forward hip position, which goes from 0 to 1 in each domain D v [28]. Details given [29]. The resulting trajectories match the human data well and are shown in [15].…”
Section: Amputee-prosthesis Model and Gait Generationmentioning
confidence: 99%
“…To design output trajectories for the amputee-prosthesis system that are invariant through impact, we use a hybrid zero dynamics condition [28] in an optimization whose solution must also satisfy the dynamics and feasibility constraints. We design the cost function to minimize the difference between the outputs (the joints) and human joint kinematic walking data obtained through motion capture [29]. The optimization yields parameters for each domain α v that define Bézier polynomials for the desired trajectories y d s,v (τ (x s ), α v ) parameterized by the state-based phase variable τ (x s ), forward hip position, which goes from 0 to 1 in each domain D v [28].…”
Section: Amputee-prosthesis Model and Gait Generationmentioning
confidence: 99%
“…The optimization solution gives parameters to define the desired trajectories y d s (τ (x s ), α) and the outputs to simulate the human side. See [26] for details. Fig.…”
Section: Human-prosthesis Simulationmentioning
confidence: 99%